How I do it: Bullet removal from head and neck regions - Baskota, D.K. (Journal of Institute of Medicine Nepal, 2007)
A retrospective, observational study to find out a reliable, simple and cost effective new technique (Needle guided technique) for exact localization and successful removal of bullets from head and neck regions was currently carried out in the Department of ENT- Head &Neck Surgery of Tribhuvan University Teaching Hospital Kathmandu, Nepal. Altogether two bullets of two patients were exactly localized and removed successfully without any complication in this region by applying this new technique. The result of this study so far indicates that “Needle guided technique” is reliable, simple and cost effective technique to localize bullets especially in head and neck regions followed by their successful removal, which is recommended to doctors working without advanced radio diagnostic support and even for those who cannot afford for the advance radio diagnosis. Journal of Institute of Medicine Vol.27(2) 2005